Hedyotis recurvata (Rubiaceae): a new species from southern Western Ghats of India - P., Jiji; K., Jeomol K.; M., Manudev K.; Sunojkumar, P. (Phytotaxa, 2023)
A new species, Hedyotis recurvata is described from Avalanche, in the Nilgiris district of Tamil Nadu, India. The details on phenology, distribution and photographs along with a comparison chart of allied species are provided here.